PELAPORAN KEUANGAN UMKM BERDASARKAN SAK EMKM (Studi Kasus pada UMKM di PD Pasar Jaya Kramat Jati) - Tina Setyaningsih; Khoirina Farina (JURNAL LENTERA BISNIS, 2021)
The purpose of this research  is to statistically examine the factors that influence the preparation of MSMEs financial reporting based on SAK EMKM at PD Pasar Jaya Kramat Jati. The data in this study are primary data, obtained through the distribution of questionnaires totaling 85. Due to special consideration in accordance with predetermined criteria, Therefore the sampling technique uses  purposive sampling in this study. Processing in the study  uses  SmartPLS 3.3.2 software. The result of  this study shows that there is evidence that the variables of  educational background  and business scale have a positive and significant impact on MSMEs financial reporting based on SAK EMKM. While other variables in this study namely  accounting understanding and do not have significant influence on MSMEs financial reporting based on SAK EMKM.Key words: SAK EMKM, Financial reporting, UMKM